Acoustic Emission Characteristics and Energy Evolution of Red Sandstone Samples under Cyclic Loading and Unloading - Tianzuo Wang; Chunli Wang; Fei Xue; Linxiang Wang; Beyene Hana Teshome; Mengya Xue (Shock and Vibration)
To explore the characteristics of rock deformation and failure under cyclic loading and unloading, the MTS815 rock mechanics test system and acoustic emission (AE) signal acquisition system were used to perform cyclic loading and unloading tests on red sandstone samples. The results showed that, compared with the uniaxial compression test, cyclic loading and unloading had a certain strengthening effect on the strength of the samples. The plastic deformation of the rock samples increased as the number of cycles increased. Based on AE signals, the cracking mode classification was analyzed on the basis of the average frequency and the rise angle of the waveforms. It was observed that the Felicity ratio gradually decreased with the increase in the stress level, which showed a cumulative damage effect. From the perspective of energy, the obvious increase of AE energy rate was mainly concentrated in the early and late stages of uniaxial compression, while the significant increase of dissipated energy rate occurred in the late stage of uniaxial compression. During the cyclic loading and unloading, most of the work done by external forces in the compaction stage and the elastic stage was converted into elastic strain energy, and dissipated energy began to gradually increase in the stage of stable fracture development. In addition, it was found that the damage evolution of the rock samples changed from slow to fast, and the dissipated energy ratio increased when failure was approaching.